Sinkronisasi Estrus dan Inseminasi Buatan pada Rusa Timor - Nalley, Wilmientje Marlene Mesang; Handarini, Ristika; Arifiantini, Raden Iis; Yusuf, Tuty Laswardi; Purwantara, Bambang; Semiadi, Gono (Jurnal Veteriner, 2012)
The objective of this experiment was to examine the fertility of timor deer (Rusa timorensis) frozensemen by artificial insemination (AI) with intracervical technique after estrus synchronization withControlled Internal Drug Release, for Goat (CIDR-G®). Six adult, healthy, and cycling hinds aged 3 to 4years were used in this experiment. The percentage of estrus hind, onset and duration of estrus wereobserved. Pregnancy diagnosis was conducted using ultrasound scanner (USG) at day 120 afterinsemination. The response of estrus was 82.22 %, the onset of estrus was 25.33 hours after CIDR®withdrawal with the length of estrus was 28 hours. The pregnancy rate at first AI trial under sedation was16.7% (1/6), at second and third without sedation was 60% (3/5) and 100% (2/2) respectively. The durationof pregnancy was 248 to 285 days; with the average calving rate was 50%. The result concludes thatinsemination in hind without sedation was better than with sedation.
Keywords: Estrous synchronization, artificial insemination, timor deer